A darwinian process: the molecular evolution of enzymes - Bertrán Rusca, Joan (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
New concepts as ambiguity, promiscuity and plasticity have allowed getting a deeper insight in the mechanism of the Darwinian process implied in the molecular evolution of enzymes. Directed evolution in the laboratory collapses the time scale for evolution from millions of years to months or even weeks due that the key processes: mutations, recombination, screening or selection are carefully controlled by the experimenter. In order to get a more meaningful vision a more enlarged scientific background is presented. The philosophical reflections focus on the increasing information in the evolution process, which goes beyond the dualism matter-spirit, and on the successive emergences. Finally some ethical and theological reflections are proposed.
Keywords: darwinian process; enzyme promiscuity; molecular evolution; information; emergence; biotechnology; creation; intelligent design